Ketidaklangsungan Ekspresi dalam Antologi Puisi “Ayat-Ayat Api” Karya Sapardi Djoko Damono: Kajian Semiotika M. Riffaterre - Nur Rahma; Mahmudah Mahmudah; Suarni Syam Saguni (Indonesian Journal of Pedagogical and Social Sciences, 2021)
Abstract. The source of data in this research is poetry from the poetry anthology